1993
DOI: 10.1021/bi00210a010
|View full text |Cite
|
Sign up to set email alerts
|

Solute diffusion in lipid bilayer membranes: An atomic level study by molecular dynamics simulation

Abstract: To elucidate the mechanism of solute diffusion through lipid bilayer membranes, nearly 4 ns of molecular dynamics simulations of solutes in phospholipid bilayers was conducted. The study, the first atomic level study of solute diffusion in a lipid bilayer, involved four simulations of an all-atom representation of a fully solvated dimyristoylphosphatidylcholine (DMPC) bilayer in the L alpha phase with benzene molecules as solutes, totaling over 7100 atoms. These simulations agree with experimental evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
118
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 68 publications
17
118
1
Order By: Relevance
“…When the value of PSA of a molecule lessened within the range from 0 to 108.80 Å 2 , its value of LogBB would increase. This was consistent with the experimental results that the more polarity it possessed, the more difficultly a molecule entered the hydrophobic environment of BBB [38]. BI as the connective index of molecular average total distance pertained to the volume parameter.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When the value of PSA of a molecule lessened within the range from 0 to 108.80 Å 2 , its value of LogBB would increase. This was consistent with the experimental results that the more polarity it possessed, the more difficultly a molecule entered the hydrophobic environment of BBB [38]. BI as the connective index of molecular average total distance pertained to the volume parameter.…”
Section: Discussionsupporting
confidence: 90%
“…A model of DMPC monolayer membrane composed of 25 DMPC molecules (5 × 5 × 1) was constructed using Material Studio and minimized for 200 steps with the smart minimizer. Here, the parameter of the single crystal of DMPC with a = 8 Å, b = 8 Å, and γ = 96.0˚ resulted in each lipid molecule with an average area of 64Å 2 similar to Stouch's research results [38]. Moreover, a layer of water (40 × 40 × 10 Å 3 ) including 529 water molecules was added to the polar side of the DMPC monolayer membrane (Figure 1).…”
Section: Blood-brain-barriersupporting
confidence: 74%
“…Since the early 1990s molecular dynamics studies of diffusion of small molecules in lipid bilayers have been extensively pursued. 2,5,6,29 These studies have shown that small solutes diffuse at different rates depending on their location in the bilayer, with high diffusion rates found in the center of the bilayer, where the membrane density is low, while much lower diffusion rates were found in the region of the headgroups. In order to get a more detailed description of the position-dependence of the diffusion process, a series of simulations of dipalmitoylphosphatidylcholine (dppc) and dmpc lipids systems were performed with a single fentanyl molecule and different numbers of oleic acid molecules, where the fentanyl molecule is constrained in the z-direction (normal to the bilayer) to certain depths in the bilayer, while still being free to move in the xy plane.…”
Section: Microscopic Diffusion Of Fentanyl In a Lipid Bilayermentioning
confidence: 99%
“…The diffusion of small hydrophobic non-electrolytes such as benzene is too fast to be measured but was investigated by molecular dynamics simulations (Bassolino-Klimas et al 1993). After insertion into the well-ordered, highly packed interfacial lipid region of the membrane (which was the ratelimiting step), benzene was shown to move from one packing defect to the next, whereby the rate of diffusion increased with increasing cis-trans isomerization of the fatty acyl chains toward the center of the membrane.…”
Section: Concept Of Passive Diffusionmentioning
confidence: 99%